2015
DOI: 10.1073/pnas.1504376112
|View full text |Cite
|
Sign up to set email alerts
|

A universal entropy-driven mechanism for thioredoxin–target recognition

Abstract: Cysteine residues in cytosolic proteins are maintained in their reduced state, but can undergo oxidation owing to posttranslational modification during redox signaling or under conditions of oxidative stress. In large part, the reduction of oxidized protein cysteines is mediated by a small 12-kDa thiol oxidoreductase, thioredoxin (Trx). Trx provides reducing equivalents for central metabolic enzymes and is implicated in redox regulation of a wide number of target proteins, including transcription factors. Desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 43 publications
3
42
0
3
Order By: Relevance
“…To complete the structural redox proteome of the CB cycle enzymes and identify the common feature behind the acquisition of TRX-mediated redox control, the crystal structures of PRK from two model species-the green alga Chlamydomonas reinhardtii and the land plant Arabidopsis thaliana-were determined and compared with those of other TRX-controlled enzymes. Our results strongly suggest that the acquisition of a TRX-targeted motif positively correlates with the acquisition of flexibility in the target proteins, consistent with the observation that the entropic contribution obtained from the reduction of the oxidized target enzyme is the main driving force of the redox control mediated by TRXs (17).…”
Section: Significancesupporting
confidence: 88%
“…To complete the structural redox proteome of the CB cycle enzymes and identify the common feature behind the acquisition of TRX-mediated redox control, the crystal structures of PRK from two model species-the green alga Chlamydomonas reinhardtii and the land plant Arabidopsis thaliana-were determined and compared with those of other TRX-controlled enzymes. Our results strongly suggest that the acquisition of a TRX-targeted motif positively correlates with the acquisition of flexibility in the target proteins, consistent with the observation that the entropic contribution obtained from the reduction of the oxidized target enzyme is the main driving force of the redox control mediated by TRXs (17).…”
Section: Significancesupporting
confidence: 88%
“…The redox-sensitive APSK in plants appears to have evolved after bifurcation of the sulfur assimilation pathway in the green plant lineage to provide a control mechanism for partitioning sulfur flow via APS into primary and specialized thiol metabolic routes in plastids (8 -11). Earlier biochemical studies on the APSK from Arabidopsis demonstrated similar redox regulation that could be mediated by E. coli thioredoxin (31), which is consistent with a common target recognition mechanism for the reduction of disulfides by thioredoxin (49). In plants, oxidative stresses increase the demand for cysteine and glutathione and activate two key enzymes (APS reductase and glutamate-cysteine ligase) in the primary pathway leading to these molecules (40, 50 -53).…”
Section: Discussionsupporting
confidence: 60%
“…Such a requirement agrees with the lower reduction potential of thioredoxin (−270 mV; Lundstrom & Holmgren, ) compared to GSH (−240 mV; Schafer & Buettner, ) and may also reflect the ability of Trx1 to bind to oxidized substrates, thereby providing a kinetic as well as a thermodynamic advantage over GSH. Indeed, it has recently been shown that Trx1 preferentially binds to conformationally restricted molecules such as those containing non‐native disulfides (Palde & Carroll, ). The ability of Trx1 to preferentially reduce disulfides in proteins supports the notion that cytosolic proteins whose function is regulated by disulfide formation are recycled by the Trx1 rather than GSH pathway (Toledano et al , ).…”
Section: Discussionmentioning
confidence: 99%